Discrimination Against Mulatto as Reflected in Faulkner’s Light in August - Tini Mogea; Salaki Reynaldo Joshua (LITERACY : International Scientific Journals of Social, Education, Humanities, 2022)
The purpose of this study is to reveal discrimination in Faulkner’s Light in August. This study is qualitative, which means that the data are in the form of words, thus the data got from the novel and other books are relevant to this research. In analyzing the data, the writer uses a mimetic approach in order to reveal discrimination in Light in August. The findings show that when slavery was embodied, these freed blacks did not automatically obtain equal rights as the whites. The white Americans have treated the blacks unequally. They have excluded the blacks from the white orphanage, schools, and colleges. Besides, they do not allow people of mixed parentage to enter the white school. People of mixed parentage, in spite of their white skin, are regarded as blacks and therefore should enter the black school. In employment, white Americans often refuse to hire black workers because of their racial prejudice of blacks as lazy, lacking in initiative, inferior and untrustworthy. In law enforcement, African Americans receive unequal legal protection. White Americans may cheat, strike, and even kill the blacks but black Americans may not. When a black man kills a white man, he will soon be sentenced to death or lynched. The blacks receive harsher sentences than white Americans and they are easily sentenced to death or lynched. White racism may destroy all the aspects of American life such as politics, culture, social relations, education, employment, and legal protection because it will array white and black Americans against each other which could eventually destroy the social structure of the United States.